PENGGUNAAN MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN MEDIA INTERAKTIF WIZER.ME TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X DI MAN 2 BONE - Riska, Riska; Ali, Mahammad; Erwing, Erwing (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: implementing a combination of LKPD and technological developments as well as a combination of technology-based games, this model is designed to provide an interactive, interesting and effective learning experience by utilizing game design principles. Methods: This research was conducted for 1 (one) month in the even semester of the 2023/2024 academic year at MAN 2 class X Bone, Tanete Riattang District, Bone Regency. The type of research used is quantitative research with an experimental approach. Results: The results show that the influence of the Game Based Learning learning model assisted by interactive media Wizer.me has a significant effect on improving the learning outcomes of class X3 students at MAN 2 Bone, compared to the lecture model and can be said to be influenced by the Game Based Learning learning model assisted by interactive media Wizer.me. Conclusion: the fact that the alternative hypothesis (H1) is accepted, it can be said that there is an influence of the use of the Game Based Learning learning model assisted by interactive media Wzer.me on the subject of Biology class X3 MAN 2 Bone. This can be seen from the results of student learning on the first test before the treatment, the average value is 72.14 while the average value of students after being given treatment is 79.00.